Selective Oxidation of Limonene over γ-Al2O3 Supported Metal Catalyst with H2O2 - Dr. Tuğba Gürmen Özçelik (International Journal of Engineering and Management Research, 2018)
Liquid phase oxidation of limonene by hydrogen peroxide over the CeO2 and Fe2O3 catalysts supported by γ-Al2O3 was reported. Etly acetate and acetone were used as solvent to investigate the effect of the solvent on the oxidation reaction. The experiments were carried out at 80 °C The conversion of limonene and the selectivities of the carvone were calculated during the 10h reaction time. According to experimental results, maximum conversion of limonene and product selectivity of carvone were obtained with CeO2-γAl2O3 catalyst as 85% and 41%, respectively end of the 10 h reaction. The XRD analysis of the CeO2-γAl2O3 catalyst were performed.